(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A growing body of research indicates that consuming small quantities of polyphenol-rich alcoholic drinks like wine or beer may be beneficial to one’s health. Scientists have long debated the effects of alcohol on immune function, finding that high doses of alcohol can directly suppress a wide range of immune responses on the one hand, and that alcohol abuse is linked to an increased incidence of a variety of infectious diseases on the other. Moderate alcohol consumption, on the other hand, appears to have a protective effect on the immune system when compared to alcohol abuse or abstinence. As a result, the relationship between alcohol consumption, immune response, and infectious and inflammatory processes is still a mystery. With this in mind, it’s important to remember that other factors, both directly and indirectly related to immune function, such as drinking habits, beverage type, amount of alcohol consumed, and gender differences, will influence the impact of alcohol consumption on the immune system. This review summarizes published research on the effects of light to moderate amounts of polyphenol-rich beverages such as wine or beer on healthy adults’ immunity.